Law and values in the European Union - Weatherill, Stephen, 1961- (Oxford : Oxford University Press, 2016)
How does the European Union (EU) function, and why does it function in this fashion? Why do states in Europe choose to co-operate, and how does the EU enable this co-operation? These key questions of EU law and more are examined and answered in this introduction to the legal integration of the EU.
This edition previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 20, 2016).
Keywords: European Union; Law -- European Union countries; European Union countries -- Foreign relations; Law; International law